SMS DISTRIBUTER BASED PATIENT APPOINTMENTS SYSTEM - Mohammad Salim Abdulrahman; Rebin B. Koshnaw; Mazin S. Al-Hakeem (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Models with advanced access in general practice have been introduced worldwide in order to enhance healthcare services throughout last decade. This has led to obtaining benefits such as eliminating waiting lists, enhancing patient’s timely access to services and lowering no show. Despite, implementing these models in Kurdistan’s public hospitals, more precisely, in places with no internet access or low internet literacy, these systems will be less used. The current paper work appointment systems introduce one of the main problems arise in hospitals which is missing appointments by the patients due to the long queues given by the secretary of doctors. In the high light of this problem, there have been several web applications developed to show the exact date of appointments, however, according to latest report by UNDP report on Iraq development more than 50 % of patients in Erbil city don’t have internet access or they don’t know how to use internet. We are proposing an optimal solution for this problem which is an SMS based patient appointment system. Patients will be notified by an SMS a day before the actual appointment after they have been to hospital and registered themselves into an online registration system by the secretary. These are carried out in practice using SMS distributer, SQL Server database and ASP.NET and C# programming languages.